Uterine Arteriovenous Malformations: Clinical Presentation and Management Outcomes. - Nida Fatima, Tanzeela Iram, Rubina Qadir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Uterine arteriovenous malformations (AVMs) are rare but potentially life-threatening vascularanomalies that can cause abnormal uterine bleeding, often following pregnancy, cesarean section, or uterine instrumentation.